Launch event of the Impact of the International Livestock Research Institute - International Livestock Research Institute (International Livestock Research Institute, 2021)
This is the launch and discussion of our new book, 'The Impact of the International Livestock Research Institute', bringing together ILRI alumni, partners, livestock champions and others who wanted to learn the role livestock plays in sustainable development. Livestock is one of the fastest growing agricultural sectors, with most growth occurring in developing countries. For over 45 years one global centre has been mandated to conduct research on leveraging the benefits and mitigating the costs of livestock production in poor countries. Learn more: https://www.ilri.org/ILRI-research-im...